Nincs királyi út - Botos, Katalin (Közép-Európai Közlemények, 2010)
Before 1990, the reform-opposition criticizes the government that they want to stimulate the capital inflow instead of real reforms. The author in her earlier work published in January 1990 underlined, that there is no royal way which is without suffering. To control the inequilibrium in the economy one has to introduce real reforms of ownership, in public financ to create a more balanced budget and liberalize the role of prices. After the political changes one political wing urged the quick privatisation saying that the state is no good owner. Because there was no financing capacity at the housholds, saving was very limited, the quick privatisation led to a high foreign ownership int he enterprise sector. The country- as other Central European Countries (CEC-s) relied havily on foreign capital both FDI and lending. It was partly necessary, partly dangerous. Technical modernisation was important but the foreign – owned firms often repatriate their profit. Hungarian GDP difers from GNI strongly, compared to OECD countries. The over-reliance on foreign capital coases problems for both economy and society.